The stability of the Pexider equation - Nikodem, Kazimierz (Annales Mathematicae Silesianae, 1991)
A stability theorem for the Pexider functional equation (1) is proved. It is an analogue of the classical theorem of Hyers [5] relating to the stability of the Cauchy functional equation.